Movement-related changes in synchronization in the human basal ganglia. - Cassidy, M; Mazzone, P; Oliviero, A; Insola, A; Tonali, P; Di Lazzaro, V; Brown, P (2002)
There is a wealth of data suggesting that behavioural events are reflected in the basal ganglia through phasic changes in the discharge of individual neurones. Here we investigate whether events are also reflected in momentary changes in the degree of synchronization between neuronal elements. We simultaneously recorded local potentials (LPs) from the subthalamic nucleus (STN) and/or ipsilateral globus pallidus interna (GPi) or scalp EEG during voluntary movements of a hand-held joystick in six awake patients following neurosurgery for Parkinson's disease. Without medication the power within the STN and the coherence between the STN and the GPi were dominated by activity with a frequency of <30 Hz. This coupling was attenuated by movement. In the presence of exogenous dopaminergic stimulation, power within the STN and coherence between the STN and the GPi was dominated by activity at 70-85 Hz, which increased with movement. The movement-related changes in coherence between the STN and EEG showed a similar pattern of pharmacological dependence, as seen subcortically. Movement-related frequency-specific changes in synchronization occur in the basal ganglia and extend to involve subcortico-cortical motor loops. The dynamic organization of activities in the frequency domain might provide a means for temporal co-ordination within and across different processing streams in the basal ganglia. This organization is critically dependent on the level of dopaminergic activity.